Penerapan Metode Inkuiri Dalam Meningkatkan Hasil Belajar IPS Terpadu - Zebua, Irene (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This study aims to determine the application of inquiry learning methods in the learning process at SMP Negeri 5 Gunungsitoli academic year 2016/2017 on the subject matter of cooperation between countries in the field of economy using inquiry method. The results of the research as follows: (1) In the first cycle of the observation of the implementation of learning process for teacher respondents through the application of inquiry methods reached an average of 67.08% are at sufficient intervals, whereas in cycle II the results of observation of the implementation of learning process for teacher respondents through the method of inquiry reached an average of 82.94% was at a good interval. Observation result of student activity during learning process in cycle I average is 48,84% is enough and in cycle II average equal to 76,92% pertained good; (2) In the first cycle of student learning outcomes of 65.27% is quite enough, whereas in the second cycle the average of student learning outcomes is 79.79% is good; (3) Percentage mastery of students 'learning outcomes in cycle I of 41.67% while the percentage of mastery of students' learning outcomes in cycle II is 86.11%. Keyword: inquiry Abstrak: Penelitian ini bertujuan untuk mengetahui penerapan metode pembelajaran inkuiri dalam proses pembelajaran di SMP Negeri 5 Gunungsitoli T.P 2016/2017 pada materi pokok kerjasama antar negara dalam bidang ekonomi dengan menggunakan metode inkuiri. Hasil penelitian sebagai berikut: (1) Pada siklus I hasil observasi pelaksanaan proses pembelajaran untuk responden guru melalui penerapan metode inkuiri mencapai rata-rata 67,08% berada pada interval yang cukup, sedangkan pada siklus yang II hasil observasi pelaksanaan proses pembelajaran untuk responden guru melalui metode inkuiri mencapai rata-rata 82,94% berada pada interval yang baik. Hasil observasi aktifitas siswa selama proses pembelajaran pada siklus I rata-rata sebesar 48,84% tergolong cukup dan pada siklus II rata-rata sebesar 76,92% tergolong baik; (2) Pada siklus I rata-rata hasil belajar siswa sebesar 65,27% tergolong cukup, sedangkan pada siklus II rata-rata hasil belajar siswa 79,79% tergolong baik; (3) Persentase ketuntasan hasil belajar siswa pada siklus I sebesar 41,67% sedangkan persentase ketuntasan hasil belajar siswa pada siklus II sebesar 86,11%. Kata kunci: inkuiri